IMPLEMENTASI MEDIA CULTURE CRAFT BERBASIS DIGITAL UNTUK MENGENALKAN NITRASIA PADA SISWA DI SEKOLAH DASAR SURABAYA - Wulandari Cahyaningrum, Ayu; Mariati, Pance; Akhwani; Sunanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the importance of introducing Indonesian traditional values to elementary school students through engaging, interactive, and technology-based learning. The use of digital learning media is expected to support students in understanding traditional values in a more meaningful and concrete way. This study aimed to describe the implementation of the digital-based Culture Craft media in introducing Indonesian traditional values to third-grade students at SDN Tenggilis Mejoyo I Surabaya.This study employed a qualitative approach with a descriptive research design.The data were collected through observations, interviews, and documentation involving the classroom teacher and third-grade students. Data validity was ensured through source triangulation and technique triangulation. The data were analyzed through data reduction, data presentation, and conclusion drawing and verification. The findings revealed that the implementation of the digital-based Culture Craft media was carried out through preparation, implementation, and closing stages of learning activities. The integration of visual elements, text, and animation created a more active learning environment and increased students’ participation during the learning process. Furthermore, the media helped students recognize the values of cooperation, responsibility, tolerance, and patriotism, as reflected in group discussions, task completion, project presentations, and students’ understanding of Indonesia’s cultural diversity. In conclusion, the digital-based Culture Craft media contributes to the introduction of Indonesian traditional values while strengthening character development among elementary school students.